Sosialisasi dan Penyusunan Rencana Strategi Marketing Mix Pada Usaha Mikro Kecil dan Menengah di Desa Subur Kecamatan Air Joman - Siregar, Aris; Sahla, Hilmiatus; Batubara, Zulfa Khairina; Aggraini, Sustika Winda; Br. Barus, Melyana; Sitorus, Eko Anuary (Maslahah: Jurnal Pengabdian Masyarakat, 2024)
Small and Medium Enterprise (SME) is a business that plays a role in development and the national economy, currently developing very rapidly. The role of business is felt to be very important because this sector is not only a source of livelihood, but also provides employment opportunities both directly and indirectly for people with low levels of knowledge and skills. This sector is very open to anyone, it can be seen that the numbers are very large and very varied. The role of Small and Medium Enterprises (SME) is also related to government efforts to reduce poverty and equalize income. In line with its development, many business actors have emerged, triggering business competition, with competition from various Small and Medium Enterprises (SME), a marketing strategy is really needed, one of the marketing strategies that supports marketing products to provide satisfaction to consumers is the use of Marketing Mix. This community service is carried out with the aim of providing knowledge about preparing Marketing Mix strategy plans for Small and Medium Enterprise (SME) actors in Subur village, Air Joman sub-district.